Possible Post‐Traumatic Focal Dystonia Associated with Tau Pathology Localized to Putamen‐Globus Pallidus. Issue 5 (8th August 2018) - Iacono, Diego; Lee, Patricia; Hallett, Mark; Perl, Daniel
Abstract: Background: Dystonia is often associated with damage to basal ganglia (BG), but neuropathological assessments of these cases are infrequent. Methods: A brain was assessed with possible post‐traumatic focal dystonia that appeared after an accident occurred during childhood. Results: Tau pathology was found within putamen and globus pallidus of the right hemisphere, and chronic traumatic encephalopathy (CTE) was observed in the cortex of the left hemisphere. No diffuse axonal injury (DAI), β ‐amyloid, ubiquitin, p62, or pTDP43 pathology was found. Conclusions: Post‐traumatic dystonia could be associated with post‐traumatic tau pathology formation. However, more cases are necessary to establish causality. The tau lesions found in the BG of this patient did not fit within CTE criteria. We hypothesize that due to the anatomo‐histological characteristics of the BG, tau pathology associated with brain traumas produce histopathological patterns different from sulcal‐tau pathology, which is the only tau pathology distribution currently accepted as pathognomonic of CTE.